(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to identify the extent of the effect of using the Polya strategy on the achievement of fourth grade middle school students in chemistry. The experimental group who study using the Polya strategy and the average scores of the control group who study in the usual way in the achievement test).